A Systematic Review of the Relationship Between School Performance and Employee Job Satisfaction: Evidence from China’s Educational Context - wang, zhengchun (Pacific International Journal, 2025)
This systematic review examines the empirical relationship between school performance and employee job satisfaction, focusing on studies conducted in China and internationally. Using a structured methodology, 39 peer-reviewed journal articles, policy papers, and empirical reports published between 2000 and 2024 were selected based on predefined inclusion criteria. Key dimensions of school performance namely, leadership, curriculum quality, resource management, and stakeholder engagement, were synthesized alongside job satisfaction components including job security, work climate, job roles, and community attachment. The review reveals a consistent positive correlation between effective leadership, resource allocation, and teacher satisfaction. However, disparities in urban-rural settings, performance pressures, and weak integration of professional development initiatives are recurring challenges. The findings highlight the bidirectional influence between institutional performance and employee satisfaction, emphasizing the need for holistic policy interventions. Future research is encouraged to explore localized contexts, such as Dongguan City, and to employ mixed-method approaches for deeper insights.